Geological Structure Exploration of Karst Collapse Column and Evaluation of Water Insulation Properties of the Mud Part - Shijian Yu; Jiyang Liu; Peng Bai; Hongtao Xu; Runshan He; Yongshen Wang; Dawei Yin (Geofluids)
In this study, the X5 KCC in Shiquan Coal Mine was investigated by means of controlled source audio magnetotelluric exploration and borehole television. In this way, the subsection geological structure of the KCC was obtained. Next, the geological and electrical characteristics of each part were analyzed, and it is concluded that the development status of the mud part under coal seam floor is the key part to judging whether water inrush will occur during working face recovery under aquifer pressure. Furthermore, the mineral compositions of purplish-red mudstone and lime mudstone were obtained by performing an X-ray diffraction experiment on the KCC interstitial materials. On this basis, the water insulation properties of the mud part were qualitatively evaluated. Finally, the tensile strength of the mud part was obtained by the Brazilian splitting method, and the water insulation ability of the mud part at the periods when the tunneling roadway and the working face passed the KCC was calculated, respectively. The research results boast guiding significance for safe recovery of the working face passing KCCs under aquifer pressure.